PENGARUH PROFITABILITAS, LIKUIDITAS TERHADAP NILAI PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA DENGAN KEBIJAKAN DEVIDEN SEBAGAI VARIABEL MODERASI - Safrie Wahyu Ramadhan; Noor Shodiq Askandar; Afifudin Afifudin (Universitas Islam Malang, 2022)
This study aims to analyze and examine the effect of financial performance, profitability, liquidity on the value of manufacturing companies on the Indonesia Stock Exchange with dividend policy as a moderating variable for 2016-2020. The sampling method used in this study is using a purposive sampling technique to obtain a sample of 70 companies. The data analysis method used in this research is multiple linear regression analysis. The results of this study explain that 1) Dividend Policy is able to influence the relationship between Profitability and Liquidity to the Firm Value variable, 2) Profitability Has a Significantly Positive Effect on Firm Value, 3) Liquidity Has a Significantly Positive Effect on Firm Value, 4) Dividend Policy is Able to Significantly Moderate the Effect of Profitability On Firm Value, 5) Dividend Policy Is Able to Significantly Moderate the Effect Of Liquidity On Firm Value.Keyword: Financial Performance, Profitability, Liquidity, and Dividend Policy